Analisis Kualitatif Tentang Persepsi Masyarakat Terhadap Penerapan Teknologi 5G di Indonesia - Friawan, Lalu; Bahuri, Nova; Hambali, Dinata (Journal of Science and Technology: Alpha, 2025)
The implementation of 5G technology in Indonesia holds significant transformative potential across various sectors such as communication, education, healthcare, and industry. However, societal acceptance of this technology is still influenced by various factors, including understanding, needs, and concerns about its impact. This study aims to analyze public perceptions of the implementation of 5G technology in Indonesia through a qualitative approach. Data were collected through in-depth interviews with respondents from diverse social, economic, and geographical backgrounds. The analysis results indicate that the public generally appreciates the potential benefits of 5G, such as high-speed internet access and support for technological innovation. Nevertheless, concerns related to costs, data security, and health impacts remain major obstacles. This study emphasizes the importance of public education, inclusive policies, and effective communication strategies to support the optimal implementation of 5G technology. These findings are expected to serve as a reference for policymakers and industry players in designing implementation strategies that are responsive to societal needs.